Upaya Peningkatan Pelayanan Administrasi Kependudukan Di Kelurahan Gebang Putih Kota Surabaya - Ervinda Rahmawati; Diana Hertati (Jurnal Pengabdian Bersama Masyarakat Indonesia, 2023)
There are many residents in Gebang Putih Village who do not have complete population documents, especially in RW 001. Through the MSIB (Certified Independent Study Internship) program, the author conducts community service by optimising population administration services in the village with several methods, namely collecting data, program implementation, and evaluation. After the community service activities carried out by the author, the number of residents who have incomplete population documents has decreased drastically. The decrease in the number of residents who do not have incomplete documents is the result of optimisation efforts that have been made by the author and village officials.